Development of acceleration measuring system with a 3-D gyroscope sensor during the flight phase in ski jumping - Sosaki, T.; Ichikawa, K.; Tsunoda, K.; Hoshino, H.; Miyake, S.; Koike, T.; Ono, M. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
In ski jumping, the aerodynamic force affects to jumpers flight length. It is important to know directly the behavior of the aerodynamic force in each individual jumper. The purpose of this study is to reveal the acceleration on the global coordinate system during the flight phase in ski jumping. Methodology: Measurements of acceleration during ski jumping were carried out by voluntary participation of three Japanese jumpers at the Hakuba normal hill in the year of 2006 summer. An accelerometer with gyroscope sensor was made by Micro Stone Co. Saku city Nagano Japan. Three directions of respective acceleration data were calculated by the data of angular velocities. An accelerometer and gyroscope were set on the back position (L1 to L3) and fixed by an elastic band. The X-direction was defined as a parallel to the anteroposterior axis of the trunk, the Ydirection to the transverse axis and the Z-direction to the longitudinal axis. The accelerations and angular velocities were calibrated just before the measurement. The acceleration data were stored in the digital memory, after the data were decomposed by the frequency of 200 Hz. FFT analyses were 256 points data set, overlapped, and Hanning window. Results: The time at the position of the edge of the take off platform was defined as the origin. The maximum amplitude of the acceleration at the initial flight phase was clearly large (over 2.5G) in each local coordinate system. The peak values of angular velocity at the initial flight phase were produced approximately 0.2 sec later than the peak accelerations. The peak power spectrums for acceleration in three directions just after the take-off were observed at almost the same frequency. The frequency was 9.37Hz. Peak power spectrums for angular velocity just after the take-off were produced in the frequencies of 9.37Hz in the x-direction, of 8.59Hz in the y- and the z-directions. A development of the peak power spectrum at the initial flight would be shown an evidence of the connection between jumper and skis. The acceleration data on the local coordinate system were reconstructed to the global coordinate system by using the angular data. The angle which was obtained by integration of angular velocity, was duplicated the angular displacement without drift. The data from the second order integration about the acceleration precisely traced jumper`s trajectory. Conclusion: Our measuring tools are useful for taking accurate acceleration in each ski jumper. The frequency in acceleration just after the take off is almost the same. The amplitude of the acceleration at the initial flight phase was clearly large. During aero phase, the value of the peak power spectrum exponentially decreases.